2013
DOI: 10.1111/pcn.12065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of psychiatric disorders in referred adolescents with Internet addiction

Abstract: Aim:To investigate prevalence and patterns of psychiatric disorders in young subjects with Internet addiction (IA).Methods: Subjects were taken from a sample of patients, aged 10-18 years old, referred to Istanbul Medical Faculty, Child and Adolescent Psychiatry Department due to a variety of behavioral and emotional problems alongside problematic Internet use. Inclusion criteria included IQ Ն70 and score Ն80 on Young's Internet Addiction Scale (YIAS). Psychiatric comorbidity was assessed using the Turkish ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
80
1
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 35 publications
10
80
1
21
Order By: Relevance
“…These results further draw the attention towards ADHD, as its association with PIU was stronger than the link between depression and PIU. These findings support the already existing literature [9,11] and add a sample from Germany, where the relationship between PIU and ADHD has only been investigated scarcely so far. Another relevant aspect as suggested by Ho et al [44] is the role of ADHD as predisposing factor of PIU, based on the onset of ADHD (at the age of 7 by clinical definition), that usually predates the incipience of PIU.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results further draw the attention towards ADHD, as its association with PIU was stronger than the link between depression and PIU. These findings support the already existing literature [9,11] and add a sample from Germany, where the relationship between PIU and ADHD has only been investigated scarcely so far. Another relevant aspect as suggested by Ho et al [44] is the role of ADHD as predisposing factor of PIU, based on the onset of ADHD (at the age of 7 by clinical definition), that usually predates the incipience of PIU.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Gamez-Guadix [15] showed in a longitudinal study over the course of one year from Spain that the depressive symptomatic at point 1 predicted an increase in PIU (here the preference for online relationships) at point 2. However, most of the studies in this field of research have been conducted in Asia [9][10][11]16,17]. As PIU seems to be culture-specific, based on different prevalences in different countries, the examination of comorbidities of PIU in different cultural circles plays an important role for clinical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that ADHD in children and adolescents is significantly associated with Internet addiction [32,[33][34][35][36][37][38]. Our results also showed that a new type of Internet overuse and addiction (FB overuse and FB addiction) are also higher among ADHD adolescents.…”
Section: Discussionsupporting
confidence: 77%
“…Farklı psikiyatrik bozuklukların internet bağımlılığın altında yatan neden olduğu veya internet bağımlılığının başka bozukluklara yol açabildiği tam aydınlatılamadığı için bu kişi-lerin klinik olarak değerlendirilmesi önem taşı-maktadır. 13,24 Türkiye'de aynı grupta internet bağımlığının zaman içindeki değişimini inceleyen ilk çalış-madır; ancak bu çalışmanın iki önemli sınırlılığı vardır. Birincisi, araştırma bir üniversitede yapıl-dığı için, araştırma sonuçları ülkedeki tüm üni-versite öğrencilerine genellenemez.…”
Section: Discussionunclassified